AOD Smelting of Austenitic Stainless 1Mn18Cr18N Protective Ring Steel - Zhang Donghai, Xu Rongchuan, Guo Chang, Xu Yong, Zhang Xiaolei, Pan Mingxu (Teshugang, 2024)
Through the thermodynamic calculation and analysis of nitrogen solubility in 1Mn18Cr18N protective ring steel， it is found that increasing the content of Cr and Mn elements in the steel can significantly improve the solubility of nitrogen. At the same time， the solubility of nitrogen increases as the molten steel temperature decreases . This paper describes the production process of 1Mn18Cr18N protective ring steel by non-vacuum induction furnace， electric furnace，AOD and LF refining， and alloying treatment with bottom blowing nitrogen， which is shorten the production time， and the composition control is quite stable. When AOD refining bottom blowing nitrogen is used for alloying， the nitrogen content in the molten steel can reach 0. 547% and the nitrogen solubility tends to be saturated. In the LF refining process， when using bottom blowing nitrogen and nitrogen-containing alloys， the nitrogen content in the steel can reach 0.68%.